Investigating EFL Teacher's Strategies and Challenges in Promoting Students' High Order Thinking Skills - Shofa Abidah; Siti Muniroh; Niamika El Khoiri (AL-ISHLAH: Jurnal Pendidikan, 2024)
Critical thinking is essential to be acquired by today's generation specifically since it is one of the skills in the 21st-century skills. Considering its importance, developing students' high-order thinking skills has become a requirement for teachers, specifically in their language learning. This study investigates an EFL teacher's strategies in promoting students' high-order thinking skills and the challenges they face in implementing it. A case study was conducted involving one junior high school teacher in Jember. The interview and classroom observation were conducted to collect the data. The data was analyzed by classifying the strategy used by the teacher using Hennessy et al.'s Scheme for Educational Dialogue Analysis and specifying the challenges faced by them through an interview. The findings of this study indicated that most strategies used by the teacher were to invite elaboration or reasoning. The challenge encountered by the teacher was the difficulties in teaching HOTS for low achiever students, difficulties in managing passive students in the classroom, and difficulties in constructing HOTS strategy in some skills in English. Therefore, more strategies to actively engage student participation in the classroom and good classroom management are needed to extend students’ high-order thinking skills.